The Use of Code-Mixing and Code-Switching on Instagram by Students of English Program at IAIN Parepare - Jasmi ilmiana; Amzah Selle; Abdul Haris Sunubi (Inspiring: English Education Journal, 2022)
The objective of the this research are to find the type of code mixing, code switching user which using two languages of english eduaction department at IAIN Parepare. This reserach will answer these main question : what kinds of code mixing and code switching used in instagram, what are the functions of code mixing and code switching used instagram. This reserach used qualitative approach, it used content analysis the data it was from students status posted mei until october 2020 the researcher collected the data by using documentation and observation cheklist the data was anaylzed the types of code mixing based poplack theory, code switching based suwito theory, analyzed what function of code mixing and code swithing on students instagram based on marasigan theory, and analyzed what reason of code mixing and code switching on students instagram based on hoffman theory.The result showed that the analysis the total data 14 unit of analysis of code switching, all three types found that 9 data (42,9%) used inter-sentential switching. It showed that inter-sentential switching is commonly use on students instagram. The type had found 3 insertion of words (14,3%). Based on the data, students status on instagram commonly used insertion of word and insertion of phrase to mix the code. The researcher found functions that used by students on instagram in order to perform both code mixing and code switching, facility expression (F7) 8 data or (38,1%). Keywords: Analysis, code-switching. Code-mixing, Instagram